(untitled) (Indian Journal of Arid Horticulture, 2013)
The Indian jujube, popularly known as ber(Ziziphus mauritiana Lamarck), is an important fruit crop grown in arid and semi arid regions of India and worldwide. Nutritionally, the fruits are rich in protein, phosphorus, calcium, carotene and vitamin C. In India, there are various factors responsible for yield losses in terms of quantity as well as quality. Of these, biotic stresses such as pests and diseases are of prime importance. Among the various insect-pests infesting ber, the stone weevil Aubeus himalayanusVoss (Curculionidae: Coleoptera) seems to be is a new threat to ber cultivation in India as in recent years severe infestation has been reported in different ber growing region viz., Anantapur (Andhra Pradesh), Rahuri (Maharashtra), Jobner (Rajasthan), Bijapur (Karnataka) and Bikaner (Rajasthan). In addition, the infestation of this pest was also reported from Bangladesh. The adult female weevil, characterized by dark brown snout, usually lays eggs on the stylar end of fruits and rarely on the distal end. The newly emerged white colour grubs enter into seed by making puncture in endocarp at immature stage and starts feeding on soft seed coat. Later it enters into endosperm moving downward and starts feeding upon inner content of the seed, and pupates within the seed by making hallow galleries. The weevil completes its life within a single fruit. The infestation results in severe fruit drop at initial stage of fruit set. The damage intensity of stone weevil varies with cultivars as varieties with larger stone are preferred over those, which have higher pulp content. Periodical monitoring of orchard for weevil incidence is essential for devising suitable strategies for efficient management of pest in time. Detection at advance stages of infestation would render it difficult to manage as pests enters into the seed.